Factors Influencing Audit Quality: With Evidence - Pouraghajan, Abbas Ali (Indian Journal of Finance, 2009)
The potential conflicts of interests among owners, managers, and other security holders create an environment in which an outside auditor may contribute significant value to investors. In fact, recent corporate scandals, such as Enron and World Com have focused the world's attention on whether audit firms are supplying audits of sufficiently high quality. On the other hand, the concern about the quality of accounting numbers and its relation with the quality of the auditing process is increasing over time, following the periodical clusters of business failures, frauds, and litigation (Chambers 1999). The auditing process is supposed to serve as a monitoring device (Wallace 1980) which will reduce managers' incentives to manipulate reported earnings. Therefore, it is hypothesized that the higher the auditing qualities lower the earnings management activities by managers, ceteris paribus. High audit quality should be associated with high information quality of financial statements because financial statements audited by high quality auditors should be less likely to contain material misstatements. The author believes that large audit firms try to supply a higher quality for protection of its brand name and reputation and limitation of tenure will increase auditor independence.